2008
DOI: 10.1111/j.1468-1331.2008.02312.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of Huntington disease in maternal plasma: direct and indirect study

Abstract: Non-invasive prenatal diagnosis of HD is possible by the analysis of fetal DNA in maternal plasma. Direct analysis of the mutation has shown higher accuracy than the haplotype analysis except for long expansions. Haplotype analysis would need to be improved for the study of Juvenile-onset HD. This diagnostic method would be limited to those couples with an affected male however this situation represents 80-90% of the pregnancies at-risk of HD. Moreover, it could be used as a confirmation test of healthy embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
0
30
1
3
Order By: Relevance
“…Therefore, NIPD will spare invasive prenatal testing in 100% of these pregnancies. Huntington's disease (Bustamante-Aragones et al, 2008e;GonzalezGonzalez et al, 2003aGonzalezGonzalez et al, , 2003bGonzalezGonzalez et al, , 2008, achondroplasia (Chitty et al, 2011;Li et al, 2004Li et al, , 2007Lim et al, 2010;Saito et al, 2000), myotonic dystrophy (Amicucci et al, 2000), and early onset primary dystonia (Meaney and Norbury, 2009) are the pathologies with a dominant inheritance pattern studied to date in maternal plasma (Table 3). -NIPD of Huntington's disease: As a reference laboratory for Huntington's disease studies, our experience in the NIPD of this pathology includes the study of 13 cases (only 6 of which have been published) (Bustamante-Aragones et al, 2008e;GonzalezGonzalez et al, 2003aGonzalezGonzalez et al, , 2003b.…”
Section: Autosomal Single-gene Disordersmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, NIPD will spare invasive prenatal testing in 100% of these pregnancies. Huntington's disease (Bustamante-Aragones et al, 2008e;GonzalezGonzalez et al, 2003aGonzalezGonzalez et al, , 2003bGonzalezGonzalez et al, , 2008, achondroplasia (Chitty et al, 2011;Li et al, 2004Li et al, , 2007Lim et al, 2010;Saito et al, 2000), myotonic dystrophy (Amicucci et al, 2000), and early onset primary dystonia (Meaney and Norbury, 2009) are the pathologies with a dominant inheritance pattern studied to date in maternal plasma (Table 3). -NIPD of Huntington's disease: As a reference laboratory for Huntington's disease studies, our experience in the NIPD of this pathology includes the study of 13 cases (only 6 of which have been published) (Bustamante-Aragones et al, 2008e;GonzalezGonzalez et al, 2003aGonzalezGonzalez et al, , 2003b.…”
Section: Autosomal Single-gene Disordersmentioning
confidence: 96%
“…Myotonic dystrophy (D) (Amicucci et al, 2000) Huntington's disease (D) (Gonzalez-Gonzalez et al, 2003a;2003b;2008;Bustamante-Aragones et al, 2008e) Achondroplasia (D) (Chitty et al, 2011;Li et al, 2004Li et al, , 2007Lim et al, 2010;Saito et al, 2000) Early onset primary dystonia I (D) ( (Tungwiwat et al, 2006) Beta-thalassemia (R) (Chan et al, 2010;Chiu et al, 2002a;Fucharoen et al, 2003;Li et al, 2009;Lo and Chiu, 2010;Lo et al, 2010;Lun et al, 2008b;Papasavva et al, 2006Papasavva et al, , 2008Tungwiwat et al, 2007;Yi et al, 2010aYi et al, , 2010b …”
Section: Referencementioning
confidence: 99%
“…Previous research has shown that cffDNA is rapidly cleared from maternal circulation after delivery; this contributed to the emerging interest in cffDNA as a potential marker for prenatal diagnosis (Romao et al, 1992;Thomas et al, 1995). Many researchers have explored the possibility of using cffDNA in the non-invasive prenatal diagnosis (NIPD) of fetal sex, RhD blood typing, aneuploidy, and single gene disorders, such as cystic fibrosis and Huntington's disease (Bustamante et al, 2008;Norbury et al, 2008;Buysse et al, 2013;Oxenford et al, 2013). cffDNA is present in very low quantities in the body; therefore, it is important to optimize cffDNA yields when considering it for clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the diagnosis of monogenic disorders, we have reported the study of different diseases (e.g., cystic fibrosis, Huntington's disease [HD], propionic acidemia, Leber congenital amaurosis and X-linked retinitis pigmentosa), applying methods routinely used in molecular diagnostic laboratories (Table 1). We have shown that the technique currently used for conventional prenatal diagnosis of HD is also sufficiently sensitive for its use in NIPD [40][41][42]. This disorder is diagnosed by measuring the size of a polymorphic (CAG)n repeat.…”
Section: Reviewmentioning
confidence: 99%
“…Different methodologies have been used for the detection of ccff DNA (i.e., conventional PCR, restriction ana lysis, quantitative fluorescence [QF]-PCR, real-time PCR and automated sequencing) (Table 1) [17,25,[31][32][33][34][35][36][37][38][39][40][41][42][43][44]. In recent years, new analytical methods have emerged, thus allowing for new advances in NIPD.…”
Section: Technical Approachesmentioning
confidence: 99%